THE EMERGENCE OF LOCAL COFFEE SHOPS IN INDONESIA AS A COUNTER TO AMERICAN CULTURE HEGEMONY - Siti Nurhasanah; Chika Dewi (Rubikon : Journal of Transnational American Studies, 2019)
After winning World War II, the United States (US) tried to spread its hegemony in almost all aspects, including culture. Starbucks has become the biggest MNC belong to the US that spreads western culture in Indonesia.  Starbucks, with its 326 outlets in Indonesia, has brought its new value to Indonesian society. In this paper, the writer would like to analyze the response of Indonesians in dealing with the cultural hegemony that Starbucks brings as the representation of the American culture. This paper uses library research as the data collection method and qualitative method in analyzing the data. The writer analyzes this case by applying the circuit of culture theory, which consists of 5 aspects: production, consumption, regulation, representation, and identity. The writer will focus on how local coffee shops adopt the management and production process from Starbucks applied in their coffee shops. The creativity of Indonesians has made new cultures are quickly adopted. The advent of Starbucks in Indonesia had stimulated the establishment of local coffee shops that are not less competitive with Starbucks as the giant coffee shop corporation. The local coffee shops can give a unique experience in enjoying a coffee just like Starbucks with its “Starbucks Experience”. The local coffee shops also can provide not only coffee, but also other products that might take the interest of customers. The local coffee shops are able to imitate, and modify Starbucks concept in local versions.Keywords: Starbucks; circuit of culture; production; local coffee; coffee culture